O reflexo do espelho não mostra a subalternidade: Drácula sob uma perspectiva pós-colonial - Faria, Raquel Juliane Ribeiro de [UNESP] (2015)
This paper aims to make a Postcolonial Reading of the Gothic novel Dracula, written by Bram Stoker. Most importantly, it is considered how the subaltern is silenced, and that how this silence reflects the characters responsible for the discourse construction in the book. For this purpose, the theories of three important writers of the Post-Colonialism, Edward Said, Homi Bhabha and Gayatri Chakravorty Spivak, were studied, as well as the enlightening ideas of Stephen Arata in The Occidental Tourist: Dracula and the Anxiety of Reverse Colonization. It also verified the construction of Orientalism in Stoker's work, and its constitutively hybrid and transparent characters due the speech manipulation with the ideological filter of the hegemonic power. This manipulation also characterizes the fragmentation in the work, which is an indication, among others, of modernity in Stoker's novel